Hadith #4745 - Sunan Abi Dawud - Anas ibn Malik; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mukhtar bin Falfal مختار بن فلفل (Sunan Abi Dawud)
Before you there will be a pond the distance between whose sides is like that between Jarbah and Adhruh.
Grade: Sahih